ANALYSIS OF VILLAGE FINANCIAL ACCOUNTING SYSTEM IN GIRIREJO VILLAGE INCOME AND EXPENDITURE BUDGET MANAGEMENT - Arung Restu Buana (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2021)
This study aims to find out how the application of village financial accounting in the context of managing the Village Revenue and Expenditure Budget (APBDes) in Girirejo Village, Tegalrejo District, Magelang Regency, Central Java Province. Furthermore, in the Village Fund Allocation (ADD) there are several activities such as planning, implementation, reporting, accountability. This research uses descriptive qualitative analysis method. The speakers consist of several resource persons such as the Village Apparatus, namely the Village Head, Carik/Village Secretary, and other staff. The data collection method by means of interviews. Based on the results of this study, the application of the accounting system in Girirejo Village, Tegalrejo District, Magelang Regency, Central Java Province still tends to be low because many village officials have only high school education levels so that knowledge about the world of accounting is still low. However, the management of the Village Revenue and Expenditure Budget (APBDes) starting from the planning, implementation, administration, reporting, and accountability stages is in accordance with applicable laws and regulations based on the principles of transparency, accountability, participatory, orderly and budgetary discipline.